To solve the equation \( z^2 + 4z - 45 = 0 \) by factoring, we need to find two numbers that multiply to \(-45\) (the constant term) and add to \(4\) (the coefficient of the linear term).
The numbers that satisfy these conditions are \(9\) and \(-5\) because:
- \(9 \times (-5) = -45\)
- \(9 + (-5) = 4\)
Now, we can factor the quadratic expression:
\[ z^2 + 4z - 45 = (z + 9)(z - 5) = 0 \]
Next, we set each factor equal to zero:
-
\( z + 9 = 0 \)
\( z = -9 \) -
\( z - 5 = 0 \)
\( z = 5 \)
So the solutions to the equation \( z^2 + 4z - 45 = 0 \) are:
\[ z = -9, 5 \]
Thus, the answer is:
\(-9, 5\)